Systemic and local inflammatory response in women with preterm prelabor rupture of membranes - Cobo, Teresa; Jacobsson, Bo; Kacerovsky, Marian; Hougaard, David M; Skogstrand, Kristin; Gratacós, Eduard; Palacio, Montse (PloS one, 2014)
OBJECTIVE: To evaluate the inflammatory pattern in maternal circulation, amniotic cavity, cervix and vagina from women with preterm prelabor rupture of membranes (PPROM) considering the occurrence of microbial invasion of the amniotic cavity (MIAC). METHODOLOGY: A prospective study was performed in 58 women with PPROM before 34+0 weeks of gestational age. Twenty-six proteins were analyzed by a multiple immunoassay in samples of amniotic fluid, serum, cervix and vagina. Association of an inflammatory response in the invasive and non-invasive samples with MIAC was investigated. RESULTS: The rate of MIAC was 36.2% (21/58). Both amniotic fluid IL-6 and cervical C-reactive protein (CRP) showed to be independent predictors of MIAC. A cut-off level of cervical CRP≥1836 pg/mL showed a detection rate of 75%, false positive rate of 19% and positive and negative predictive values to predict MIAC of 67% and 87%, respectively. There were no independent biomarkers of MIAC either in the serum or vaginal compartment. CONCLUSION: A cervical inflammatory response mediated by CRP was observed in PPROM women with MIAC. Evaluation of serum or vaginal samples did not add valuable information regarding the outcome evaluated.
Keywords: vagina; C-Reactive Protein; Inflammation; Fetal Membranes, Premature Rupture; interleukin-6; těhotenství; předčasná porodní činnost; Interleukin-6; plodová voda; C-reaktivní protein; zánět; Gestational Age; cervix uteri; Prospective Studies; Adult; grampozitivní bakteriální infekce; gramnegativní bakteriální infekce; Amniotic Fluid; gestační stáří; Infant, Newborn; ženské pohlaví; novorozenec; mykózy; Humans; prospektivní studie; Pregnancy; Mycoses; Gram-Positive Bacterial Infections; Gram-Negative Bacterial Infections; předčasný odtok plodové vody; Vagina; dospělí; Female; Obstetric Labor, Premature; Cervix Uteri; lidé